Progressive symmetric erythrokeratoderma: A rare case report - Nibedita Patro; Maitreyee Panda; Mrutunjay Dash; Subhransu Sekhar Jena; Madhuchhanda Mohapatra (Wolters Kluwer Medknow Publications, 2016)
Erythrokeratodermas are a rare group of genetic disorders presenting early in childhood as erythematous, hyperkeratotic plaques on the skin. There may be associated neurological involvement. A 12-year-old boy presented with symmetric keratotic plaques on the body since infancy. Psoriasis and pityriasis rubra pilaris were ruled out after histopathological examination of the skin. We are reporting a case of progressive symmetric erythrokeratoderma with classical lesions but can be missed due to unawareness.